THE PROBLEMS OF THE TRANSITION OF CRAFT ENTERPRISES OF UZBEKISTAN TO A MARKET ECONOMY AT THE END OF THE 20TH - BEGINNING OF THE 21ST CENTURIES - Sokolova Lyudmila Mikhailovna (Sciental Journals Publishing, 2025)
The article on the example of two enterprises of the Ferghana Valley - the Rishtan plant of art ceramics and the Namangan factory of art products considers the problems of the transition of craft enterprises of Uzbekistan to a market economy in the late XIX - early XX centuries. During this period, these enterprises faced a sharp change in consumer demand, competition from foreign consumer goods, a lack of related raw materials previously supplied from neighboring countries and other negative economic phenomena, which led them to bankruptcy and liquidation.